Error Mastery in Alliance Transport Megaprojects - Love, Peter; Matthews, Jane (2022)
Human error is a major source of rework, with a project's culture setting the tone for its response and how it cooperates and shares information. This article examines how a program alliance's error culture, which forms part of a transport megaproject, mitigates its errors and rework. We undertake a series of semi-structured interviews to make sense of the experiences of alliance participants about why and how rework occurs, its assessment, and if knowledge sharing occurs when it arises. Our analysis reveals that the alliance effectively utilizes elements of an error management culture to communicate and share knowledge. However, we find the alliance's learning capacity is constrained by its inability to capture and analyze rework-related knowledge, preventing it from building resilience to error. Consequently, we propose a collection of principles that an alliance can draw upon to create an error mastery mindset enabling it to manage its rework risks and unexpected events. The benefits of an error mastery mindset are threefold as it provides the ability to: 1) better support people's well-being; 2) anticipate what might go wrong; and 3) adapt and learn about circumstances where errors and rework occur and re-establish work practices after an adverse event.